2018
DOI: 10.1039/c8ra04977g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of Pb/Sn/Al laminated composite anode for zinc electrowinning

Abstract: The use of Pb/Sn/Al composite anode materials has been limited due to the thermodynamic immiscibility between Pb and Al sheets during the welding process. Thus, herein, Sn has been added between Pb and Al sheets to fabricate a Pb/Sn/Al laminated composite via vacuum hot-pressing welding (at a temperature of 230C for 12 h under 0.5 MPa). Furthermore, the interfacial microstructure and mechanical and electrical properties are investigated. Good metallurgical bonding has been realized due to the addition of Sn, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The characteristic peaks of Pb-BTC at 10°–30° 2θ° disappeared, instead a new broad peak appeared at 20°–28° 2θ° (dark yellow line in Figure a) which attributed to the loss of crystallinity in the Pb-BTC structure. In addition, the new narrow peak at 30° (dark yellow line in Figure a) could be assigned to the diffraction peak of Pb 0 , which is formed during the cycles. The XRD pattern continuously changed after 1000 cycles (navy line in Figure a).…”
Section: Resultsmentioning
confidence: 96%
“…The characteristic peaks of Pb-BTC at 10°–30° 2θ° disappeared, instead a new broad peak appeared at 20°–28° 2θ° (dark yellow line in Figure a) which attributed to the loss of crystallinity in the Pb-BTC structure. In addition, the new narrow peak at 30° (dark yellow line in Figure a) could be assigned to the diffraction peak of Pb 0 , which is formed during the cycles. The XRD pattern continuously changed after 1000 cycles (navy line in Figure a).…”
Section: Resultsmentioning
confidence: 96%
“…The overpotential and catalytic activity of an electrode are directly affected by its electrical conductivity, and good electrical conductivity indicates low overpotential, fast chemical reaction, and high catalytic activity. 32 The catalytic activity of the composite is high enough to reduce the cell voltage during zinc deposition. Based on the analysis in Section 3.1.5, the CFT6 sample has the best conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…There are a large number of solid solutions of β-Sn and a small amount of solid solutions of α-Pb in the diffusion reaction zone of the Pb side according to the component analysis in Table II and the binary phase diagram for Pb-Sn. 44,47 However, the diffusion reaction between Sn and Al is not obviously produced; it is a simple mechanical occlusion and has some rifts in local regions because the oxide film on the local surface of Al hinders the reaction between Al and Sn at 230 °C for 1 h, as shown in Fig. 4b.…”
Section: Resultsmentioning
confidence: 99%
“…This has become a technical bottleneck and key technology to be solved urgently for the preparation of lead-aluminium composite materials. 44 Zhu Peixian 45 studied the effect of Bi on the preparation and performance of Pb-Al laminated composite electrode materials, and the results showed that metallurgical bonding between Pb and Al was realized by the introduction of transition element Bi. Pb-Bi-Al layered composites have excellent electrochemical properties and have important development and application prospects.…”
mentioning
confidence: 99%